2011
DOI: 10.1364/ome.1.000658
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of nonlinear optical properties of ZnO micro and nanocrystals for biophotonics

Abstract: The defect and impurity states in ZnO nanocrystals synthesized using the plasma arc technique can be modified to optimize the nonlinear optical properties for optoelectronic and biophotonic applications. Highly efficient second harmonic signals over a wide range of near-infrared wavelengths, spanning from 735 nm-980 nm, has been observed and can be used in biological imaging. The use of further high energy excitation ranging from 700 nm-755 nm leads to two-photon absorption and yields broadband two photon emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 22 publications
(43 reference statements)
1
21
0
Order By: Relevance
“…A slope close to 2 on the log–log plot indicated a nonlinear two‐photon absorption process. At the same time, second‐harmonic generation and hyper‐Rayleigh scattering, observed in case of MPM of zinc oxide and silver nanoparticles, are ruled out as the mechanisms underlying the observed Zn(PT) 2 PL as signals generated by these processes are spectrally shifted relative to the excitation wavelength shift . No spectral shift in the emission wavelength of Zn(PT) 2 was observed when the excitation wavelength shifted.…”
Section: Resultsmentioning
confidence: 90%
“…A slope close to 2 on the log–log plot indicated a nonlinear two‐photon absorption process. At the same time, second‐harmonic generation and hyper‐Rayleigh scattering, observed in case of MPM of zinc oxide and silver nanoparticles, are ruled out as the mechanisms underlying the observed Zn(PT) 2 PL as signals generated by these processes are spectrally shifted relative to the excitation wavelength shift . No spectral shift in the emission wavelength of Zn(PT) 2 was observed when the excitation wavelength shifted.…”
Section: Resultsmentioning
confidence: 90%
“…Very recently, use of less toxic and biodegradable polymers during synthesis of ZnO NPs has attracted a lot of research attention due to their potential applicability in targeted drug delivery, bioimaging, and in biophotonic devices [40,41]. Use of biodegradable capping agent such as poly vinyl alcohol (PVA) during synthesis of ZnO NPs has been studied [42,43] and it has been observed that surface-capping by PVA leads to hydrophobicity, enhanced compatibility with organic phases, UV-shielding ability of ZnO NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Among these properties, the optical properties of ZnO nanowires or NRs have been the focus of many studies because this kind of nanoobjects can be easily synthesized and has potential applications in making optoelectronic devices. In recent years, the nonlinear optical properties of ZnO nanoobjects have attracted much attention owing to their possible applications in the field of biophotonics [23][24][25]. Under the excitation of a femtosecond (fs) laser in the near infrared region, upconverted signals such as second harmonic generation (SHG) [26] and two-photon-induced luminescence (TPL) [27][28][29] can be generated in ZnO nanoobjects, making them attractive and promising candidates for bioimaging.…”
Section: Introductionmentioning
confidence: 99%